Critical race narratives : a study of race, rhetoric, and injury - Gutiérrez-Jones, Carl (Critical America., 2001)
The beating of Rodney King, the killing of Amadou Diallo, and the LAPD Rampart Scandal: these events have been interpreted by the courts, the media and the public in dramatically conflicting ways. Critical Race Narratives examines what is at stake in these conflicts and, in so doing, rethinks racial strife in the United States as a highly-charged struggle over different methods of reading and writing. Focusing in particular on the practice and theorization of narrative strategies, Gutiérrez-Jones engages many of the most influential texts in the recent race debatesincluding The Bell Curve, America in Black and White, The Alchemy of Race and Rights, and The Mismeasure of Man. In the process, Critical Race Narratives pursues key questions posed by the texts as they work within, or against, disciplinary expectations: can critical engagements with narrative enable a more democratic dialogue regarding race? what promise does such experimentation hold for working through the traumatic legacy of racism in the United States? Throughout, Critical Race Narratives initiates a timely dialogue between race-focused narrative experiment in scholarly writing and similar work in literary texts and popular culture.